The Analysis of Optimal Portfolio on Investment Decision Using Single Index Model on LQ45 Stocks (Listed on Indonesia Stock Exchange for The Period 2022-2024) - Norma, Norma; Surwanti, Arni; Rahmawati, Alni (SAFE-Network, 2025)
This research aims to examine the construction of an ideal portfolio using a single index approach in the LQ45 sector for the years 2022-2024. This study uses a quantitative descriptive analysis methodology, utilizing secondary data and purposive sampling procedures. The research findings indicate the creation of an ideal portfolio that includes 12 equities with a single index strategy. The stocks, ranked by their allocation in the portfolio, are Indofood CBP Sukses Makmur Tbk (ICBP), Mitra Adiperkasa Tbk (MAPI), Perusahaan Indofood Sukses Makmur Tbk (INDF), Unilever Indonesia Tbk (UNVR), Sumber Alfaria Trijaya Tbk (AMRT), Bank Syariah Indonesia Tbk (BRIS), AKR Corporindo Tbk (AKRA), Bank Mandiri (Persero) Tbk (BMRI), Bank Central Asia Tbk (BBCA), United Tractors Tbk (UNTR), Jasa Marga (Persero) Tbk (JSMR), and Bukit Asam Tbk (PTBA). ICBP is the largest part of the portfolio, accounting for 18.5%. Twelve optimal portfolios are projected to yield a return of 0.020830 or 2.08%. The portfolio risk that investors must face for their investments is 0.000892, equivalent to 0.09%. This research can help investors in building an optimal portfolio. Investors can distribute their capital across various stocks to optimize returns at a certain level of risk. However, this research does not differentiate between the preference for analysis methods other than the single index model, and further research could use other indices besides LQ45 and compare the results.